1987
DOI: 10.1037/0735-7044.101.3.427
|View full text |Cite
|
Sign up to set email alerts
|

Intratympanic injection of sodium arsanilate (atoxyl) solution results in postural changes consistent with changes described for labyrinthectomized rats.

Abstract: Intratympanic injections of sodium arsanilate (atoxyl) have been shown to produce vestibular dysfunction in the rat. Unilateral and bilateral dysfunction can be distinguished by changes in the animals' postures. These changes are consistent with changes described for unilateral or bilateral labyrinthectomized rats. The intratympanic injection technique offers a simple yet effective alternative to labyrinthectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 3 publications
(3 reference statements)
3
32
0
Order By: Relevance
“…We noted a similar failure of this "landing" posture in TTX-treated rats during assessments made when transferring rats to and from their home cages. The profile of behavioral changes we observed following bilateral transtympanic injection TTX was consistent with that reported following sodium arsanilate administration or surgical labyrinthectomy Wu, 1936, 1937;Horn et al, 1981;Chen et al, 1986;Hunt et al, 1987;Shoham et al, 1989;Stackman and Taube, 1997). Finally, all rats appeared to fully recover vestibular function, as assessed by the contact-righting test and from our observations of their behavior.…”
Section: Vestibular Functionsupporting
confidence: 75%
See 2 more Smart Citations
“…We noted a similar failure of this "landing" posture in TTX-treated rats during assessments made when transferring rats to and from their home cages. The profile of behavioral changes we observed following bilateral transtympanic injection TTX was consistent with that reported following sodium arsanilate administration or surgical labyrinthectomy Wu, 1936, 1937;Horn et al, 1981;Chen et al, 1986;Hunt et al, 1987;Shoham et al, 1989;Stackman and Taube, 1997). Finally, all rats appeared to fully recover vestibular function, as assessed by the contact-righting test and from our observations of their behavior.…”
Section: Vestibular Functionsupporting
confidence: 75%
“…Injections were made using a 25-μl Hamilton syringe. TTX produces a near immediate, but transient, abolition of neural activity within cranial nerve VIII (Beitz et al, 1995), and behavioral changes commensurate with those observed following bilateral labyrinthectomies or transtympanic injection of the vestibular toxin, sodium arsanilate (i.e., head dorsiflexion, a failure of contactrighting, flattened posture with forelimbs and hindlimbs abducted, increased tendency to locomote backwards, and hyperreactivity to handling; Horn et al, 1981;Hunt et al, 1987;Kaufman et al, 1992). The transtympanic TTX injection procedure was also used to examine the anatomical and electrophysiological effects in the cochlear nucleus following VIIIth cranial nerve blockade in the chick (Canady and Rubel, 1992) and gerbil (Pasic and Rubel, 1989).…”
Section: Inactivation Of the Vestibular Apparatusmentioning
confidence: 99%
See 1 more Smart Citation
“…These data indicate that although unilateral surgical and arsanilate-induced labyrinthectomies disrupt rotation-induced changes in the activity of brainstem vestibular circuitry, brainstem vestibular nuclei remain intact. More importantly, Hunt et al (1987) showed that bilateral intratympanic injections of sodium arsanilate in rats resulted in postural changes commensurate with changes observed after bilateral surgical labyrinthectomies. These behavioral changes included increased head dorsiflexion, flattened posture with limbs adducted, and an increased tendency to locomote backward and are indicative of vestibular dysfunction.…”
Section: Methodsmentioning
confidence: 92%
“…Levasseur et al first reported a reduction in bone mineral density of the femoral metaphysis in rats after 1 month of chemically induced vestibular deficiency [78,79]. This model used bilateral transtympanic sodium arsenilate injections to disturb vestibular function, causing vestibular deficiency that was accompanied with a series of abnormal spontaneous behaviors.…”
Section: Vestibular Outputs Participate To Bone Homeostasis Regulatiomentioning
confidence: 98%